The gospel embodied in African traditional religion and culture with specific reference to the cult of ancestor veneration and the concept of salvation : an inculturation hermeneutic - Shabangu, Andries (2013)
In Africa, as everywhere else in the world, the interpretation of the gospel message takes place in a particular and unique context. This means that in doing theology one should take into account the spirit and the gospel message, but also the culture of the people the message is communicated. During the Graeco-Roman period (First century Mediterranean world) the proclamation of the gospel message could not ignore the culture of the Romans, Greek and Jews. It is therefore argued in this study that the reading and interpretation of the gospel message in Africa should seriously take into consideration the African religio-cultural cues. Therefore, the current researcher calls this hermeneutical paradigm, inculturation hermeneutic. In the first chapter of this thesis, the problem posed is that while many Africans today are exposed to modern education, traditional thought is still the source of the basic world-view. Even though a greater majority of Africans are Christianized, they still adhere to their traditional religious customs and practices such as the veneration of ancestors and visiting traditional doctors. These questions are investigated using the inculturation hermeneutic approach. The gospel features embedded in the traditional African culture are examined. Some of the features are the aspect of birth, marriage, attributes of God, the role of traditional healers and sacrifice. These features show that African traditional culture respected the birth of a child. This was considered to be a gift from God. Therefore all necessary rituals were performed to ensure that the child learns all what is expected of it. The child becomes a member of society and is able to live harmoniously with other people and with God. Marriage became an institution respected as basis of procreation, another gift from God. The attributes of God in African culture show that African traditional people knew God as Creator and sustainer of life. The researcher manages to demonstrate that these aspects of African traditional life have embedded or enshrined features that are in the gospel message and which could be made explicit and highlighted in proclaiming the Gospel in an African context. The cult of ancestor veneration has been investigated. Evidence from a variety of scholars indicates that Africans never worship ancestors. The cultural practices that Africans perform aim at demonstrating their faith in God. They are symbolic in nature. However, uninformed readers may interpret these rituals as secular and of no religious value. The different rituals are therefore explained and discussed in detail. The attempt in discussing the cult of ancestor veneration is not to validate this practice. The researcher endevours to show that the cult embodies an important element of the Gospel mediatorship. Salvation is another concept that has also been investigated. When analyzed and interpreted within the African cultural context, this aspect also demonstrates the embodiment of gospel features. Salvation is approached holistically, that is, the health of the human body as well as the spirit are taken as a whole. Some case studies of African communities are examined to establish how these communities understand salvation. Some biblical texts are cited to illustrate points of contact or similar lines of thinking, where both biblical and African communities express their faith in God. These texts are in no way intended to compare the two religions or put them on equal footing. This would result in one being used as a yardstick for the other. I think scholars should interpret each religion in its own context and evaluate its embodiment of gospel features. This means that each religion has its own unique way whereby it embodies the gospel message. And in this thesis, the submission is that African traditional culture and religion embodies gospel features. === Thesis (DPhil (Biblical and Religious Studies))--University of Pretoria, 2006. === Biblical and Religious Studies === unrestricted